Wegener Granulomatosis with Oral Involvement as Primary Manifestation: A Case Study - Mahdokht Rashed; Pegah Mosannen Mozaffari; Abbas Javadzadeh; Mehrdad Radvar; Nooshin Mohtasham; Sedigheh Modarres Mousavy (Mashhad University of Medical Sciences, 2017)
Introduction: Wegener Granulomatosis is a rare multisystemic disease with an unknown cause, characterized by necrotic granulomatous lesions in respiratory tract, systemic vasculitis in small arteries and veins and necrotizing glomerulonephritis. Wegener can affect any organ including kidneys, eyes or other organs but classically affects upper and lower respiratory tract. One of the rare but important signs of this disease is oral involvement, generally occurring in 6-13% of patients, however, oral involvement as the primary manifestation of disease, occurs in only 5-6% of cases. The most common oral manifestation is strawberry gingivitis. Patients: Our patient was a 35 year-old man with gingival bleeding during brushing which began approximately 45 days before referring to the department of oral and maxillofacial diseases, Mashhad Dental School. In intraoral examination, his gingiva had a papillomatous appearance and was purple in color (strawberry appearance). Due to the presence of strawberry appearance in absence of plaque, primary diagnosis of Wegener granulomatosis was established and the patient was referred for histopathological evaluation. In laboratory tests, C-ANCA was positive and P-ANCA was negative. Finally, diagnosis of Wegener granulomatosis was confirmed and his treatment was started. Rheumatologic condition of patient's lungs was evaluated by chest X-ray and CT-scan and blood tests, biochemistry tests and urine analysis were performed for the patient. He did not have pulmonary or renal involvement. In our study, the patient was followed up after 1, 2 and 11 months from the first visit. Discussion: Up to now, few reports have been published on Wegener disease with oral involvement and in most of these articles, Wegener was diagnosed after respiratory symptoms and kidney or other organs involvement. Only in few studies was Wegener diagnosis confirmed on the basis of oral symptoms and gingival involvement. Immediate and aggressive administration of immunotherapy treatments are required due to the fatal nature of the disease as the survival rate of patients with untreated WG is low and 90% of these patients die within 1 year after respiratory or kidney involvement .